Autochthonous malaria in Brazil outside the Amazon: Emergence, zoonotic transmission and implications for disease control - Beatriz Pires da Silva; Ricardo Lourenço-de-Oliveira; Jacqueline de Aguiar Barros; Patrícia Brasil; Cláudio Tadeu Daniel-Ribeiro; Maria de Fátima Ferreira da Cruz (One Health)
Although human malaria is endemic in the Brazilian Amazonian region, autochthonous cases are registered regularly outside this region in areas under the couverture of the Atlantic Forest biome. The infecting species in the Atlantic Forest was initially believed to be the classical Plasmodium vivax. However, these locations have epidemiological characteristics that contribute to maintaining zoonotic monkey malaria, showing a great adaptation to different hosts, and many years later, it was discovered that almost all human malaria cases in the Atlantic Forest correspond to P. simium zoonosis. This review reported the history of discovering human infections by parasites originating from non-human primates in Brazil. It also examines epidemiology and underscores the need for specific preventive measures in the malaria elimination era. The data gathered so far have demonstrated that several factors enable zoonotic disease transmission in these areas. Given the facilitating ecological aspects involved and the scarce knowledge of the disease by the populations of the non-endemic area, this scenario adds difficulty to the challenge of eliminating malaria in Brazil.